A STUDY ON CONSUMER PERCEPTION TOWARDS ECO FRIENDLY PRODUCTS IN KANYAKUMARI DISTRICT - ABILASRIN, B.; Farveen, H. SABEENA (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of the study is to analyze the consumers’ perception on various aspects of eco-friendly products and assess the factors influencing preference to purchase eco-friendly products in Kanyakumari District. Multi-stage sampling method has been used in this research for collection of samples. Cluster sampling method was used for selecting the sample in the first stage. In this method, six taluks of Kanyakumari district has been selected viz., Thovalai, Agasthees waram, Kalkulam, Vilavan code, Tiruvattar, and Killiyur. In the next stage, the researcher found consumers who are using eco-friendly products through convenient sampling method. For the present study, the universe comprises of the consumers, who are utilizing eco-friendly products in Kanyakumari district. The sampling units were selected by covering the six taluks of Kanyakumari district. The size of sample was 150 consumers who are utilizing eco-friendly products. The study reveals that the consumer of eco-friendly product consume them for maintaining the good health which ranks first followed by the fresh and natural which ranks second and quality of the product which ranks third based on their opinions. These three reasons hold the top three ranks for the usage of the eco- friendly products in the study area based on the responses given by sample consumer.